Ravenstein Revisited: The Analysis of Migration, Then and Now - Philip Rees; Nik Lomax (Comparative Population Studies, 2019)
In 1876, 1885 and 1889, Ernst Ravenstein, an Anglo-German geographer, published papers on internal and international migration in Britain, Europe and North America. He generalized his findings as “laws of migration”, which have informed subsequent migration research. This paper aims to compare Ravenstein’s approach to investigating migration with how researchers have studied the phenomenon more recently. Ravenstein used lifetime migrant tables for counties from the 1871 and 1881 censuses of the British Isles. Data on lifetime migrants are still routinely collected but, because of the indeterminate time interval, they are rarely used to study internal migration. Today, internal migration measures from alternative sources are used to measure internal migration: fixed interval migrant data from censuses and surveys, continuous records of migrations from registers, and “big data” from telecommunications and internet companies.